A critical review of the behavioral, neuroimaging, and electrophysiological studies of co-activation of representations during word production. (February 2020) - Nozari, Nazbanou; Pinet, Svetlana
Abstract: A large body of behavioral, neuroimaging, and electrophysiological studies have investigated the consequences of co-activation of representations during word production. Despite such an amazing body of empirical data, it remains unclear how the production system handles co-activated items. In this paper, we review this evidence in a systematic way, and point out three common problems in the interpretations attached to these data. We then discuss alternative approaches which might be more fruitful in understanding the links between such data and the processes of spreading activation, selection, monitoring and control in language production. Highlights: We review behavioral and neural evidence for the co-activation of words in picture naming. We point out some problematic assumptions in interpretations. We discuss alternative explanations/approaches.